Road surface characteristics : their interaction and optimisation : report - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development ; Washington, D.C. : OECD Publications and Information Center [distributor], 1984)
'This report examines economical ways to improve road surfaces to reduce traffic noise and fuel consumption while preserving high safety and driving comfort standards.'--P. [4] of cover
Published also in French under the title: Caracteristiques de surface des revetements routiers : leur interaction et leur optimisation
Includes bibliographical references
Keywords: Pavements -- Skid resistance; Traffic noise; Pavements -- Maintenance and repair; Surfaces (Technology)